"Truth Behind Bars" Reflections on the Fate of the Russian Revolution - Kellogg, Paul (Athabasca University Press, 2021)
Just north of the Arctic Circle is the settlement of Vorkuta, a notorious camp in the Gulag internment system that witnessed three pivotal moments in Russian history. In the 1930s, a desperate hunger strike by socialist prisoners, victims of Joseph Stalin's repressive regime, resulted in mass executions. In 1953, a strike by forced labourers sounded the death knell for the Stalinist forced labour system. And finally, in the late 1980s and early 1990s, a series of strikes by new, independent miners' unions were central to overturning the Stalinist system. Paul Kellogg uses the story of Vorkuta as a frame with which to re-assess the Russian Revolution. In particular, he turns to the contributions of Iulii Martov, a contemporary of Lenin, and his analysis of the central role played in the revolution by a temporary class of peasants-in-uniform. Kellogg explores the persistence and creativity of workers' resistance in even the darkest hours of authoritarian repression and offers new perspectives on the failure of democratic governance after the Russian Revolution.